2019
DOI: 10.1186/s43159-019-0006-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of urethral mobilization and advancement after anterior hypospadias surgery

Abstract: Background: In hypospadias surgery, despite continued refinement of various surgical procedures, there is no completely satisfactory technique in terms of complications and cosmesis. In recent literature, urethral mobilization and advancement (UMA) is gaining popularity in the management of distal penile hypospadias with no or very low complication rate as compared to all other techniques. The aim of this study is to share our results by using UMA in the management of anterior hypospadias with or without chord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Haider N and colleagues witnessed 0% UCF in their study. 13 Similar to our finding, many other studies by Gite VA et al, Chakraborty AK et al and Hassan HS et al reported that none of their patients developed UCF after urethral mobilization and advancement granuloplasty. [14][15][16] Age is also a determinant of outcome in hypospadias surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Haider N and colleagues witnessed 0% UCF in their study. 13 Similar to our finding, many other studies by Gite VA et al, Chakraborty AK et al and Hassan HS et al reported that none of their patients developed UCF after urethral mobilization and advancement granuloplasty. [14][15][16] Age is also a determinant of outcome in hypospadias surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Five cases had hematoma, and one had an infection; all were managed conservatively. The authors concluded that urethral mobilization and advancement result in good cosmetic and functional outcomes and can be utilized for distal hypospadias repair with a low incidence of complications, especially urethrocutaneous fistula [ 18 ]. Edan reported that the urethral mobilization technique is a good choice for distal hypospadias repair.…”
Section: Discussionmentioning
confidence: 99%
“…This technique with proven benefits and effectiveness, in the terms of cosmesis and functional outcomes, is recommended for the management of anterior hypospadias by various studies. 10,11,12,13 In 1994, Snodgrass first reported the tubularized incised plate urethroplasty. 14 The Snodgrass technique has become the optimal surgical option to repair anterior hypospadias.…”
Section: Introductionmentioning
confidence: 99%